The effectiveness of specialist neuroscience care in severe traumatic brain injury: A systematic review. (August 2014) - Fuller, Gordon; Pallot, David; Coats, Timothy; Lecky, Fiona
Abstract Background. UK trauma services are currently undergoing reconfiguration, but the optimum management pathway for head-injured patients is uncertain. We therefore performed a systematic review to assess the effects of routine inter-hospital transfer and specialist neuroscience care on mortality and disability in patients with non-surgical severe traumatic brain injury injured nearest to a non-specialist acute hospital. Methods. A protocol was registered with PROSPERO (CRD42012002021) and review methodology followed Cochrane Collaboration recommendations. A peer reviewed search strategy was implemented in an exhaustive range of information sources, including all major bibliographic databases, between 1973 and July 2013. Selection of eligible studies, extraction of relevant data and bias assessment were then performed by two independent reviewers. In the absence of homogeneous effect estimates at low risk of bias a narrative synthesis was pre-specified. Results. Four cohort studies, including a total of 4688 patients, were identified as potentially eligible after screening and bias assessment. Confounding by indication, arising from selective transfer of less severely injured patients, was the main limitation of included studies, with overall risk of bias rated as high for both mortality and disability effect estimates. Adjusted odds ratios for mortality favoured secondary transfer, ranging from 1.92 (95% CI 1.25–2.95) to 2.09 (95% CI 1.59–2.74). No convincing association was observed between non-specialist care and unfavourable outcome with a conditional odds ratio of 1.13 (95% CI 0.36–3.6). Conclusions. There is limited evidence supporting a strategy of secondary transfer of severe non-surgical traumatic brain injury patients to specialist neuroscience centres. Randomised controlled trials powered to detect clinically plausible treatment effects should be considered to definitively investigate effectiveness.